The Relationship between Household Physical Condition with Incidence of Toddler’s Acute Respiratory Infection in Surabaya - I Gusti Agung Putu Mahendra; Farapti Farapti (Jurnal Berkala Epidemiologi, 2018)
Background : Acute Respiratory Infection (ARI) is one of the main causes of high rates of mobility and mortality in infants in developing countries in the world. In 2015 the death rate from respiratory problems was 920,136 people, the most common in South Asia and Africa. Purpose : This study aims to analyze the relationship between the physical condition of the house and the smoking behavior of family members with the incidence of ARI in infants in Sidotopo, Surabaya. Methods: This research was an observational analytic study using cross sectional design. The sample size uses simple random sampling technique where all existing data and meet the inclusion and exclusion criteria have the same opportunity to be selected as samples. This study used chi square statistical test to determine the relationship between the physical condition of the house and the incidence of ARI Results: There is a relationship between lighting (PR = 3.35; p-value = 0.01), ventilation (PR = 5.75; p-value = 0.01), kitchen smoke holes (PR = 4.05 ; p-value = 0.01), roof of the house (PR = 3.07; p-value = 0.02), smoking behavior (PR = 5.63; p-value = 0.01) with ARI incidence and not there was a relationship between the wall of the house (PR = 0.64; p-value = 0.68) with the incidence of ARI. Conclusion: There was an relationship between the physical conditions of the house (lighting, ventilation, kitchen smoke holes, roofs of houses) and smoking with incidence of ARI in infants at Sidotopo Village.